Visitor in a modern museum: navigation, attraction, interaction - Sarna, Aliaksandr J. (Journal of the Belarusian State University. Sociology, 2026)
This article examines the features of the museum’s communication activities in the context of the formation and development of a culture of participation. It shows how the introduction of digital multimedia technologies and Internet resources into museum practice allows for the implementation of new formats of interaction with the audience based on the principles of common values, joint creativity, interactivity and involvement. An assessment is made of the possibilities of effective museum activities aimed at satisfying the interests of the public and forming a community of museum supporters ready to contribute to its development in modern conditions. A comparative analysis of the websites of the National Art Museum and the Belarusian State Museum of the History of the Great Patriotic War is carried out based on a comparison of the basic structural and functional elements that make up the content of these resources and the key instrumental and technical parameters that contribute to the full-fledged operation of the websites of these institutions.